UTILITY THEORY APPLICATIONS THROUGH THE CONCEPT OF INNOVATION ADOPTION IN THE MARKETING PROGRAM OF FARMERS' DOCTORS - farhan ratna; Endy Gunanto Marsasi (Politeknik Negeri Ambon, 2023)
PT Central Biotech Indonesia is a company with rolling technology that has a Farmer Doctor Program which aims to be able to get maximum customers by using direct product management and being able to satisfy customers. The farm doctor who will be run is able to attract customers with the quality of the company's products. This research was conducted with the aim of evaluating and assisting companies in promoting products in the marketing department. The method used to analyze this research is qualitative, which is carried out by observing directly, in-depth interviews, collecting documentation, and secondary data carried out at the company. From the research that has been done in marketing the product, it is less effective in maximizing the application of marketing carried out in marketing the company's products. Research conducted in companies can evaluate programs using utility theory with the application of Adopt Innovations which are implemented in conducting communications at PT Central Biotech Indonesia in supporting farmer doctors.